2023
DOI: 10.1186/s12871-023-02022-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evaluation of the independent analgesic efficacy of dexmedetomidine

Abstract: Background Dexmedetomidine has analgesic properties, but the intraoperative analgesic effect of dexmedetomidine is often masked by the effects of other general anaesthetics. Therefore, the degree to which it reduces intraoperative pain intensity remains unclear. The objective of this double-blind, randomised controlled trial was to evaluate the independent intraoperative analgesic efficacy of dexmedetomidine in real-time. Methods This single-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…found in a randomized controlled trial on the effects of dexmedetomidine and midazolam on cough and quality of recovery after partial and total laryngectomy that dexmedetomidine is an effective alternative drug in reducing cough and hemodynamic changes, and has a lower incidence of adverse events during the anesthesia recovery period after partial or total laryngectomy [39]. Similarly, an RCT study on the real-time evaluation of the independent analgesic efficacy of dexmedetomidine by XH Wang et al found that dexmedetomidine has an independent analgesic effect, and systemic administration as an auxiliary drug is more effective than midazolam, providing a better analgesic effect without serious side effects [40]. In addition to its sedative and anti-delirium effects, dexmedetomidine has been discovered to reduce inflammatory response, stress, promote postoperative gastrointestinal function recovery, and reduce postoperative chills after cesarean section, among other benefits [41] [42] [43] [44].…”
Section: Sedative Drug Selectionmentioning
confidence: 99%
“…found in a randomized controlled trial on the effects of dexmedetomidine and midazolam on cough and quality of recovery after partial and total laryngectomy that dexmedetomidine is an effective alternative drug in reducing cough and hemodynamic changes, and has a lower incidence of adverse events during the anesthesia recovery period after partial or total laryngectomy [39]. Similarly, an RCT study on the real-time evaluation of the independent analgesic efficacy of dexmedetomidine by XH Wang et al found that dexmedetomidine has an independent analgesic effect, and systemic administration as an auxiliary drug is more effective than midazolam, providing a better analgesic effect without serious side effects [40]. In addition to its sedative and anti-delirium effects, dexmedetomidine has been discovered to reduce inflammatory response, stress, promote postoperative gastrointestinal function recovery, and reduce postoperative chills after cesarean section, among other benefits [41] [42] [43] [44].…”
Section: Sedative Drug Selectionmentioning
confidence: 99%
“…Previous studies also revealed that the application of dexmedetomidine combined with LAs in nerve and fascia blocks could accelerate block onset, prolong block duration, enhance analgesic effects and significantly reduce opioid consumption (37,38). The locking mechanism could be as follows: Dexmedetomidine is an imidazole derivative with a prolonged analgesic action (39). It has been reported that it can promote vasoconstriction, delay the absorption of LAs and prolong the effect of Las (40).…”
Section: Selection Of Anesthetics and Adjuvants For Espbmentioning
confidence: 99%